Expression of Serum PSA, Nesfatin-1, and AMH in Patients with Polycystic Ovary Syndrome - Wang, Yan; Ma, Xiaorong; Luo, Jiashou; Wang, Xiaoyan; Han, Lu (Cellular and Molecular Biology, 2022)
Insulin resistance and hyperandrogenism are the leading causes of polycystic ovary syndrome (PCOS). Therefore, it has great significance to study the expression levels of PSA, nesfatin-1, and AMH. To provide some reference for clinical diagnosis and treatment of polycystic ovary syndrome (PCOS), the expression levels of PSA, nesfatin-1, and AMH in serum of patients with polycystic ovary syndrome (PCOS) were investigated. The experimental group consisted of 200 patients with polycystic ovary syndrome treated in Shanghai Huashan Hospital from July 2018 to July 2019. The control group consisted of 150 healthy women without pregnancy. The PSA, nesfatin-1, and AMH levels in serum were detected by chemiluminescence immunoassay (CLIA) and enzyme-linked immunosorbent assay (ELISA). The serum levels of prostate-specific antigen (PSA) and anti-Mullerian hormone (AMH) were 16.53 ± 0.67pg/ml and 10.75 ± 4.02pg/ml in the experimental group (PCOS patients), which were significantly higher than those in the control group (3.27 ± 0.43pg/ml and 5.18 ± 1.84pg/ml, respectively), while the inhibitive factors in the experimental group (1.89 ± 0.99mg/ml) were significantly higher than those in the control group (1.10 ± 0.97mg/ml). There was no significant difference in nesfatin-1. The levels of PSA and nesfatin-1, nesfatin-1, and AMH and the levels of PSA and AMH in patients with polycystic ovary syndrome were positively correlated, and the differences were statistically significant. The levels of PSA, nesfatin-1, and AMH in patients with polycystic ovary syndrome of different ages were different, and the differences were significant and negatively correlated with the age increasing. PSA, nesfatin-1, and AMH levels in patients with polycystic ovary syndrome were significantly different from those in control nonpregnant women. There was a certain correlation between the levels of PSA, nesfatin-1, and AMH, and age. The results have specific clinical reference significance for the diagnosis and treatment of patients with polycystic ovary syndrome.